Domoljubje in državljansko "prijateljstvo" - Klampfer, Friderik (Ars et humanitas, 2025)
In his theory of justice, John Rawls connected moral arbitrariness and undeservedness roughly as follows: if I cannot take credit for a certain property of mine, then I am not (any more than anyone else) morally entitled to the benefits of possessing, and making use of, that trait. Citizenship is typically assigned based on features that are morally arbitrary in the above sense, most commonly the place of birth and/or one’s parents’ nationality. And yet, although citizenship (of a particular country) is morally undeserved in the above sense, only a few theorists question the national legislation and the social policies that systematically favour natives over foreigners. In this arti-cle, I critically examine attempts to base patriotism on mutual concern and respect, considered constitutive of personal friendships, where bias towards someone is not only morally unproblematic but hailed as morally exemplary. Indeed, if friendship can generate mutual moral obligations and moral reasons for action, even though friendships are typically formed in a morally arbitrary way, why not also see in a patriot a person who (at least within political communities governed by democratic rule) in some sense “befriends” all her fellow citizens and, as a result, owes certain obligations just or primarily to them? However, a more thorough inquiry into the normative basis of ordinary, interpersonal friendship reveals this kind of “civic friendship” as a misconceived and potentially dangerous theoretical fiction, even in morally idealized political formations. In short, we can relax, as Slovene citizens we will not need to “befriend” strangers and political foes after all.
Keywords: Državljanstvo; friendship; justice; moral arbitrariness; moralna naključnost; Patriotizem; pravičnost; prijateljstvo; Schwarzenbach, Sibyl